Health information needs of professional nurses required at the point of care - Esmeralda Ricks; Wilma ten Ham (AOSIS, 2015)
Background: Professional nurses work in dynamic environments and need to keep up to date with relevant information for practice in nursing to render quality patient care. Keeping up to date with current information is often challenging because of heavy workload, diverse information needs and the accessibility of the required information at the point of care.   Objectives: The aim of the study was to explore and describe the information needs of professional nurses at the point of care in order to make recommendations to stakeholders to develop a mobile library accessible by means of smart phones when needed.   Method: The researcher utilised a quantitative, descriptive survey design to conduct this study. The target population comprised 757 professional nurses employed at a state hospital. Simple random sampling was used to select a sample of the wards, units and departments for inclusion in the study. A convenience sample of 250 participants was selected. Two hundred and fifty structured self-administered questionnaires were distributed amongst the participants. Descriptive statistics were used to analyse the data.   Results: A total of 136 completed questionnaires were returned. The findings highlighted the types and accessible sources of information. Information needs of professional nurses were identified such as: extremely drug-resistant tuberculosis, multi-drug-resistant tuberculosis, HIV, antiretrovirals and all chronic lifestyle diseases.   Conclusion: This study has enabled the researcher to identify the information needs required by professional nurses at the point of care to enhance the delivery of patient care. The research results were used to develop a mobile library that could be accessed by professional nurses.